Critical Thinking Skills in Physics Learning of Students at SMAN 8 Makassar - Muhammad Ikhbar Ihsan; Helmi Helmi; Khaeruddin Khaeruddin (Universitas Lambung Mangkurat, 2024)
This research aims to analyze critical thinking skills in students' physics learning at SMAN 8 Makassar. It is descriptive research employing a survey method. The research subjects are 271 students from the 10th grade at SMAN 8 Makassar, distributed across nine classes. Students' critical thinking skills are measured using a multiple-choice test instrument with indicators such as interpretation, analysis, and inference. The data collection technique used is a critical thinking skills test consisting of multiple-choice questions covering critical thinking indicators. The researcher developed these questions and underwent validation by experts and empirical validation processes. The expert validation results show that the test instrument is valid with a score above 0.75. The research results are analyzed using descriptive statistical analysis, indicating that students' critical thinking skills are still in the low category. The critical thinking skills level for interpretation is 29.97%, for analysis is 31.30%, and for inference is 38.73%. This implies that teachers must strive for innovative teaching methods to empower students' critical thinking skills. The implications of this research are expected to provide support and opportunities for teachers to improve the quality of the learning process, enabling students to develop critical thinking skills in solving physics problems and producing high-achieving students.